WHY FOCUSING ON ONE THING IS KEY: HOW IT REALLY WORKS FOR BIG SUCCESS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In today's super competitive world, where we're flooded with information, trying to do a lot of different things (diversification) often stops people from reaching the very top. This article looks closely at the "One Thing" idea, created by Gary Keller and Jay Papasan, as a serious plan for getting really rich. By bringing together ideas like the Pareto Principle (the 80/20 rule), how our brains handle too much information, and how things grow fast, this study suggests that becoming a multi-billionaire isn't about doing many things okay. Instead, it's about going incredibly deep, one step at a time.
Keywords: Strategic Prioritization, The One Thing, Pareto Principle, Fractal Productivity, Cognitive Load Theory, Attention Residue, Geometric Progression, Multibillion-Dollar Wealth Creation, Deep Work, Opportunity Cost, Lead Domino Effect, Economic Efficiency.